2011
DOI: 10.2214/ajr.10.6154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iopamidol-370 Versus Iodixanol-320 on Coronary Contrast, Branch Depiction, and Heart Rate Variability in Dual-Source Coronary MDCT Angiography

Abstract: Iopamidol-370, with its higher iodine concentration, provided greater vascular contrast of the arterial coronary tree and improved depiction of anatomic detail without significantly impacting cardiac heart rate during coronary MDCT imaging, as compared with iodixanol-320.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Indeed, the study by Becker et al 6 showed no significant difference between iomeprol and iodixanol in terms of HR variation during MDCT-CA, whereas other studies reported a reduction of arrhythmias and patient discomfort 7 and a more favorable HR response during scanning with iodixanol 7,8 than with iomeprol 7 and iopamidol. 8 Although several advancements in MDCT-CA and stent technologies further reduced the number of nonassessable stents that improve diagnostic performance, beam-hardening artifacts caused by metallic struts may still impair stent lumen visualization and quantification of lumen narrowing. 1e3 We hypothesized that iodixanol-320 might improve coronary stent assessment with MDCT-CA as a result of the lower-iodine concentration that may lead to a reduction of beam-hardening artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the study by Becker et al 6 showed no significant difference between iomeprol and iodixanol in terms of HR variation during MDCT-CA, whereas other studies reported a reduction of arrhythmias and patient discomfort 7 and a more favorable HR response during scanning with iodixanol 7,8 than with iomeprol 7 and iopamidol. 8 Although several advancements in MDCT-CA and stent technologies further reduced the number of nonassessable stents that improve diagnostic performance, beam-hardening artifacts caused by metallic struts may still impair stent lumen visualization and quantification of lumen narrowing. 1e3 We hypothesized that iodixanol-320 might improve coronary stent assessment with MDCT-CA as a result of the lower-iodine concentration that may lead to a reduction of beam-hardening artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-iodine concentration CM have been considered good contrast agents for MDCT-CA, providing higher intracoronary attenuation, 5,6 recent studies found some advantages of dimeric, iso-osmolar, lower-iodine concentration iodixanol-320 such as reduction of arrhythmias, less patient discomfort because of heat sensation, and more favorable behavior of heart rate (HR) during the scan. 7,8 We hypothesized that the use of iodixanol-320 would be particularly useful for coronary stent assessment with MDCT-CA because its use is likely associated with an attenuation of beamhardening artifacts, as a result of its lower iodine concentration. Thus, the aim of the present study was to prospectively compare the effects on stent evaluability, image quality, patient heat sensation, premature heart beats (PHBs), and HR response during scanning with the use of CM with a low-osmolar, high-iodine concentration (iomeprol-400) or an iso-osmolar, lower-iodine concentration (iodixanol-320) in patients undergoing evaluation of coronary stents with the use of MDCT-CA.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that iodixanol showed less significant HR changes during cardiac angiography [10,11]. Recently, Christensen et al [12] reported there was a significant HR deceleration for the iodixanol 320 during contrast administration, compared to iopamidol 370. In our study, iodixanol 320 showed less HR changes compared to iohexol 350 during the scan, which may influence the diagnostic accuracy and interpretability of cardiac CT angiography.…”
mentioning
confidence: 99%
“…Our study confirmed that Iodixanol resulted high image quality with the lowest rates of adverse 4 events, such as flushing and heart rate variability. Several studies reported that iodixanol showed less HR changes during cardiac angiography than iopamidol (12)(13)(14). In a randomized study of 300 patients, iodixanol 320 showed less HR changes compared to iohexol 350 during the scan.…”
mentioning
confidence: 99%